2015
DOI: 10.3329/bpj.v17i1.22317
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Anti-inflammatory Activities of Ethanolic Extract of Clerodendrum inerme (L.) Gaertn.

Abstract: Clerodendrum inerme (L.) Gaertn. (Verbenaceae) is very popular among the traditional practitioners in Bangladesh for the treatment of local pain and inflammation, skin diseases, topical burns etc. However, so far no scientific study has been carried out which may support its uses in traditional medicine. In the present study, we evaluated the possible analgesic and anti-inflammatory activities of the ethanol extract of C. inerme for the first time. Analgesic activity was assessed by using acetic acid-induced w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…With this purpose several preparations rich in antioxidant flavonoids or purified flavonoids have been investigated (Somasundaram & Oommen, 2013). Clereodendrum inerme, for example, exerts anti-inflammatory actions that have been attributed mainly to its flavonoid constituents (Khanam et al, 2014;Somasundaram & Oommen, 2013). Tamarindus indica seed extracts, rich in procyanidins, show protective efficacy against arthritis-associated oxidative damage (Sundaram et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With this purpose several preparations rich in antioxidant flavonoids or purified flavonoids have been investigated (Somasundaram & Oommen, 2013). Clereodendrum inerme, for example, exerts anti-inflammatory actions that have been attributed mainly to its flavonoid constituents (Khanam et al, 2014;Somasundaram & Oommen, 2013). Tamarindus indica seed extracts, rich in procyanidins, show protective efficacy against arthritis-associated oxidative damage (Sundaram et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Methanol extract of C. inerme leaves is reported to inhibit sub-chronic inflammation in cotton pellet-induced granuloma in mice (Yankanchi and Koli, 2010). Recently, ethanol extracts of C. inerme exhibited anti-inflammatory in carrageenan-induced paw edema and xylene-induced ear edema (Kalavathi and Sagayagiri, 2014;Khanam et al, 2014). Such in vivo anti-inflammatory activities of C. inerme indicated the presence of anti-inflammatory agents.…”
Section: Introductionmentioning
confidence: 96%
“…The plant is used in ayurvedic | P a g e medicine for the treatment of various diseases such as rheumatism, asthma, stomach pains, hepatitis, skin disease, tumours, etc. (Kirtikar and Basu, 1975;Muthu et al, 2006) Pharmacological studies have showed that C. inerme leaves have analgesic and antiinflammatory (Amirtharaj et al, 2010;Khanam et al, 2014), antidiabetic (Rajeev et al, 2012, antipyretic (Thirumal et al, 2013, mosquito larvicidal (Kalyanasundaram and Das, 1985, hepatoprotective (Chakraborthy and Verma, 2013), antifungal (Sharma and Verma, 1991), antimicrobial (Anandhi and Ushadevi, 2013;George and Pandalai, 1949), antiviral (Mehdi et al, 1997) and anticancer (Manoharan et al 2006;Chouhan et al, 2018;Kalavathi et al, 2016) activities. Phytochemical investigation of different parts of the C. inerme revealed the presence of glycosides, anthraquinones, proteins, phenolics, flavonoids, saponins, tannins, iridoids, diterpenes, triterpenes, sterols, steroids, carbohydrates, fixed oils, volatile oils, lignin, etc (Prasad et al, 2012;Tanu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%